The Effect of Stop Motion Learning Media on Learning Motivation - Heryanto Nur Muhammad; Taufiq Hidayat; Mochamad Ridwan; Sapto Wibowo (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to determine the effect of stop motion media on learning motivation. This research uses quantitative. The sample used is class XI as many as 45 students. The sampling technique is purposive sampling. The instrument used is a questionnaire of 27 statements for learning media and 26 statements for learning motivation with a Likert scale. The results of the research obtained are stop motion learning media has an effect of 9.1% on learning motivation. The conclusion in this study is that stop motion learning media can be used as a solution to increase students' learning motivation